Primary intradural Hodgkin lymphoma of the conus medullaris and cauda equina: case report - Timothy J Williamson; Michael Wang; Jonathan Clark; Julia Williams; Armin Drnda (CNS Oncology)
Primary Hodgkin lymphoma of the central nervous system is an exceedingly rare condition with very few cases reported in the literature. Isolated intradural involvement of the spine is rarer still, with only two prior cases located in the extramedullary cervical and lumbosacral spine. We present a 48-year-old female who was presented with back pain, radiculopathy and a short history of sphincter disturbance and was subsequently found to have a lobulated homogenously enhancing exophytic lesion involving the conus medullaris and cauda equina on magnetic resonance imaging. Histopathological examination demonstrated the features of classic Hodgkin lymphoma. In this report, we present a case of primary intramedullary Hodgkin lymphoma involving the conus medullaris and cauda equina.